1902 Ohio Gen. and Local Acts 23, Extraordinary Sess.,§§An Act to Provide for the Organization of Cities and§Incorporated Villages . . . and to Repeal§All Sections of the Revised Statutes Inconsistent Herewith,§§ 7,§pt. 11 (vol. 96) - (:unkn) unknown (My University, 1902)
To regulate the transportation, keeping and sale of gunpowder and other explosives or dangerous combustibles and materials and to provide or license magazines for the same.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER